2019
DOI: 10.3390/su12010133
|View full text |Cite
|
Sign up to set email alerts
|

Energy Management Practices’ Determinants in Greek Enterprises

Abstract: The implementation of energy management over recent decades has been considered to be particularly important for companies wishing to save energy resources, to tackle the issue of climate change, and, at the same time, maintain their competitive edge in an ever-changing environment. The main objective of this article is to identify and analyse all of those critical factors that may affect the implementation of effective energy management practices by Greek enterprises. A questionnaire survey was conducted to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Abdelaziz et al [154] discussed three pathways to improve energy efficiency: regulation, technology, and management. Energy and environmental management play an important role in contemporary challenges for manufacturing companies [155][156][157][158]. This study addresses this issue and illustrates how to support GWP.…”
Section: Discussionmentioning
confidence: 97%
“…Abdelaziz et al [154] discussed three pathways to improve energy efficiency: regulation, technology, and management. Energy and environmental management play an important role in contemporary challenges for manufacturing companies [155][156][157][158]. This study addresses this issue and illustrates how to support GWP.…”
Section: Discussionmentioning
confidence: 97%
“…Our studies have revealed that there are few identifiable key components that IEnM should have-planning/strategy, operation/implementation, controlling, organization, and culture, as depicted in Fig. 1 [18], [19], [20], [21], [22]. The details of each of these components are presented next.…”
Section: Industrial Energy Managementmentioning
confidence: 89%
“…The questionnaires used in the research were adapted from [26,[152][153][154][155][156][157] and the modified questionnaire was given to industrial and academic experts for validation purposes. After obtaining feedback from experts, the questionnaire underwent an improvement process where certain items were revised to remove ambiguity.…”
Section: Questionnairementioning
confidence: 99%